2014
DOI: 10.1177/0022034514551770
|View full text |Cite
|
Sign up to set email alerts
|

NOD2 Contributes to Porphyromonas gingivalis–induced Bone Resorption

Abstract: The NOD-like receptors are cytoplasmic proteins that sense microbial by-products released by invasive bacteria. Although NOD1 and NOD2 are functionally expressed in cells from oral tissues and play a role triggering immune responses, the role of NOD2 receptor in the bone resorption and in the modulation of osteoclastogenesis is still unclear. We show that in an experimental model of periodontitis with Porphyromonas gingivalis W83, NOD2-/- mice showed lower bone resorption when compared to wild type. Quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 42 publications
0
28
1
2
Order By: Relevance
“…It has been reported that NOD1 and NOD2 mediate sensing of periodontal pathogens, including P. gingivalis , in human embryonic kidney cells (Okugawa et al ., ) and human periodontal ligament fibroblasts (Liu et al ., ). NOD2 has also been reported to play a role in alveolar bone resorption induced by P. gingivalis (Prates et al ., ). In endothelial cells, NOD1 has been linked to monitor various pathogenic bacteria, like Chlamydophila pneumoniae (Opitz et al ., ), and Listeria monocytogenes (Opitz et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been reported that NOD1 and NOD2 mediate sensing of periodontal pathogens, including P. gingivalis , in human embryonic kidney cells (Okugawa et al ., ) and human periodontal ligament fibroblasts (Liu et al ., ). NOD2 has also been reported to play a role in alveolar bone resorption induced by P. gingivalis (Prates et al ., ). In endothelial cells, NOD1 has been linked to monitor various pathogenic bacteria, like Chlamydophila pneumoniae (Opitz et al ., ), and Listeria monocytogenes (Opitz et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that NOD1 and NOD2 mediate sensing of periodontal pathogens, including P. gingivalis, in human embryonic kidney cells (Okugawa et al, 2010) and human periodontal ligament fibroblasts (Liu et al, 2014). NOD2 has also been reported to play a role in alveolar bone resorption induced by P. gingivalis (Prates et al, 2014). In endothelial cells, NOD1 has been linked to monitor A B C D Figure 5 Nuclear factor-jB (NF-jB) and P38 mitogen-activated protein kinase (MAPK) signaling pathways play a role in human umbilical vein endothelial cell activation following Porphyromonas gingivalis invasion.…”
mentioning
confidence: 99%
“…Alveolar bone loss elicited by Porphyromonas gingivalis shares many features of lysis attending OM. Cytokine release (166) as well as induction of RANKL downstream of TLR2 and NOD2 are the prominent pathways leading to osteoclast activation in periodontitis (167,168). IL-17 is also markedly increased in periodontitis and appears to be an important factor in both inflammation and osteolysis of the periodontal tissue (169).…”
Section: Infection-associated Osteolysismentioning
confidence: 99%
“…Previous studies have reported that P. gingivalis (Burns et al ., ; Jain et al ., ) and T. forsythia (Myneni et al ., ) are recognized by TLR2, Campylobacter rectus is recognized mainly by TLR4 (Arce et al ., ), and many PRRs (including TLR2, TLR4, and NOD1) were suggested to mediate cytokine expression upon Fusobacterium nucleatum and Aggregatibacter actinomycetemcomitans stimulation (Park et al ., ). Recent studies indicate that NOD2 and TLR9 are also involved in P. gingivalis infection (Prates et al ., ; Kim et al ., ). Overall, these studies suggest that PRRs play important roles in the host response against periodontal pathogens and emphasize the importance of further characterizing the immune response to other newly identified pathogens involved in periodontitis.…”
Section: Introductionmentioning
confidence: 99%